Comparative proteomics of pistils and anthers from self-incompatible and self-compatible almonds by iTRAQ and 2D-nano-LC ESI-MSMS - Gómez E.M.; Dicenta F.; Martínez-García P.J.; Ortega E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
It is known that the cultivated almond [Prunus dulcis (Miller) D.A. Webb] exhibits gametophytic selfincompatibility controlled by the S locus. This locus contains two genes that codify for the S-RNase and SFB proteins, which seem to determine the specificity of incompatibility. However, recent studies support the involvement of other unidentified proteins in the incompatibility system of this species. A few proteomic studies have tried to identify candidates to modifier factors of the incompatibility system in Prunus sp. using comparative proteomics of pollinated pistils. However, there are no studies in which pollen and un-pollinated pistils from self-incompatible and self-compatible individuals are compared. To identify proteins differentially expressed in the pistils and anthers of almonds with an identical S-haplotype but different incompatibility phenotypes, iTRAQ and 2D-nano-LC ESI-MSMS were carried out. Seventeen and 23 proteins were identified as differentially expressed in anthers and pistils, respectively. Most of these proteins had a metabolic or stress resistance and defence function, and some of them had been associated to pollen development, pollen dynamics or to pollen-pistil interactions. These results provide proteomic profiles of differential expression in mature pistils and pollen, and could also serve as a reference for other comparative proteomic studies in almond and in other species with the same incompatibility system.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)